Results of a community-based survey of construction safety climate for Hispanic workers. (September 2015) - Marin, Luz S.; Cifuentes, Manuel; Roelofs, Cora
Abstract : Background: Hispanic construction workers experience high rates of occupational injury, likely influenced by individual, organizational, and social factors. Objectives: To characterize the safety climate of Hispanic construction workers using worker, contractor, and supervisor perceptions of the workplace. Methods: We developed a 40-item interviewer-assisted survey with six safety climate dimensions and administered it in Spanish and English to construction workers, contractors, and supervisors. A safety climate model, comparing responses and assessing contributing factors was created based on survey responses. Results: While contractors and construction supervisors' ( n = 128) scores were higher, all respondents shared a negative perception of safety climate. Construction workers had statistically significantly lower safety climate scores compared to supervisors and contractors (30·6 vs 46·5%, P <0·05). Safety climate scores were not associated with English language ability or years lived in the United States. Conclusions: We found that Hispanic construction workers in this study experienced a poor safety climate. The Hispanic construction safety climate model we propose can serve as a framework to guide organizational safety interventions and evaluate safety climate improvements.